Wayfindings system in library / Nur Fashihah Mohd Latif - Mohd Latif, Nur Fashihah (2014)
A signage system can be more than just a sign. It can give a place its identity and figures and lettering can be attractive adornments in themselves if properly designed. The basic rules of signage design is signs must be visible but not distracting, informative but not unwisely, and concise but not confusing. The elements that can be varied and exploited to encapsulate, as much information as possible and fit the requirement is color, typography, pictograms and icons. The library is a place to gain knowledge and focus point for community. Most of the library in Malaysia lack of environmental graphic A good way finding system gives strong indicators of where the user is and how to get to her destination from her present location. Way finding problems occur when decisions cannot be executed. In a poor way finding system, the user does not have enough information to decide his or her course of action. Further, users may also become so frustrated with the environment that they will not return. If a building has good way finding features, the user should have a positive experience when reaching their destination. Where one of my task to design some signs and information board. The latter should ideally prevent people from getting lost and also create a visual identity.